Intrapreneurial intention mediates between individual entrepreneurial orientation, entrepreneurial self-efficacy and intrapreneurial behaviour - Wijetunge, Wijetunge Arachchige Deepani Sajeewa; Yusoff, Siti Khalidah Binti Md; Azam, Ferdous; Tham, Jacquline (International Journal of Management and Sustainability, 2024)
The purpose of the study is to investigate the influence of Individual Entrepreneurial Orientation (IEO) and Entrepreneurial Self-efficacy (ESE) towards Intrapreneurial Behaviour (INB). Entrepreneurial Intention and Entrepreneurial Behaviour have been a growing interest of the scholars in research in entrepreneurship literature during the last three decades. Rigorous reviews on intentions and behaviors only appeared in limited number of studies to investigate the mediating effect of Intrapreneurial Intension. Further, this study examines the mediation effect on Intrapreneurial Intention (INI) between IEO, ESE, and INB. Thus, this study attempts to test an extended model to understand the individual behaviour of using TPB and IEO. The methodology is quantitative, followed by a survey method. The sample contained 120 small tea exporting companies in Sri Lanka, registered with the Sri Lanka Tea Board (SLTB). The data were collected from Owners and Managers of those companies. The results discovered that there is a significant positive impact of IEO, ESE, and INI on INB. Also, it was registered that Intrapreneurial Intention mediates the direct relationships and implies that IEO and ESE can enhance INB through Intrapreneurial intentions. In this scenario, INI plays an important role in influencing INB. Therefore, tea industry, the government, regulatory bodies and policymakers use these findings to enhance the INB among small tea exporters in Sri Lanka. This study provides useful insights to small tea exporters in Sri Lanka on how to enhance intrapreneurial behavior through psychological factors.